THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. BANK DANAMON TBK, AHMAD YANI MAKASSAR BRANCH - Muhammad Erfan; Muhammad Bakri; Gazali Amin (Universitas Ichsan Sidenreng Rappang, 2023)
This research aims to partially test and analyze the influence of organizational culture and organizational commitment on employee performance at PT. BANK DANAMON Tbk Ahmad Yani Makassar Branch and to find out the variables that have a dominant influence on employee performance at PT. BANK DANAMON Tbk Ahmad Yani Makassar Branch. Data collection uses primary data obtained from questionnaires using the Slovin sample. The population is all employees at PT. BANK DANAMON Tbk Ahmad Yani Makassar Branch had 119 employees, while the sample taken was 54 respondents. The results of the questionnaire have been tested for validity and reliability, and also tested for classical assumptions in the form of normality assumptions and heteroscedasticity assumptions. The data analysis method uses multiple regression techniques. The research results show that the first and second hypotheses are accepted because they show positive and significant hypothesis results, this means that Organizational Culture and Organizational Commitment have a partially positive and significant effect on Employee Performance at PT BANK DANAMON Tbk Ahmad Yani Makassar Branch. The third hypothesis is accepted because it shows that the Organizational Commitment variable has a dominant influence on Employee Performance at PT. BANK DANAMON Tbk Ahmad Yani Makassar Branch.